Software smartens up data manipulation. - Masi, C.G (IEEE spectrum)
The paper considers how software products for data acquisition, analysis, and visualization are starting to get their acts together in their latest releases. Such coordination was just a dream a few years ago. One reason for the change is that software developers no longer look at what they create as isolated products intended for a specific mission, but as components within larger enterprises